Structural formation and leaching behavior of mechanically activated lignite fly ash based geopolymer - Mucsi, Gábor; Szenczi, Ágnes; Molnár, Zoltán; Lakatos, János (Journal of Environmental Engineering and Landscape Management, 2016)
Geopolymers are inorganic polymers which can be produced by the reaction of aluminium silicate oxides and alkaline silicates in an alkaline medium. Nowadays, silicate bearing wastes, such as fly ash or slag and other byproducts of power stations are very common raw materials for geopolymers. In our research a lignite type fly ash was mechanically activated in a high energy density mill (HEM) for different retention time, and geopolymer specimens were produced from these materials. After determining the optimal fly ash fineness, the concentration and composition of the alkaline activator solution were also investigated. The highest compressive strength was reached using fly ash with 2 m2/g specific surface area, activated with a mixture of Na-K silicate (water glass) and naoh solution. The total dosage of alkaline activators to the fly ash was 40 m/m%, the naoh activator of 12 M solution represented 25 m/m%, while Na-K silicate 75 m/m%. Then, the leaching properties of the main components and the mobility of toxic elements of the produced geopolymers were tested in distilled water, 1M acetic acid and 1M hydrochloric acid as well. The lowest mobility of the elements was obtained in most cases by the activator containing 100m/m% Na-K silicate solution (water glass) using the mechanically activated fly ash.